Hubungan kelengasan tanah dan fluktuasi curah hujan dengan dinamika puncak panen mangga gedong gincu - Nono Sutrisno; S. Setyo Wardoyo (Jurnal Ilmu Tanah dan Air, 2018)
The Relations Of Soil Moisture Contains and Rain Fluctuation with Dynamics PeakHarvest of Mango Gedong Gincu (Nono Sutrisno and S. Setyo Wardoyo): Mango gedong gincu is a fruit whose market is good for Indonesia and export, is a typical fruits of Indramayu and Majalengka District, West Java. The purpose of this research is to study the relationship between soil moisture content and rainfall fluctuation with harvest season and peak of mango gedong gincu, to develop marketing strategy of mango gedong gincu and to determine the development strategy of mango gedong gincu based on the difference of harvest time. The research was conducted in Krasak Village, Jatibarang Sub-district; Sliyeg Lor Village, Sliyeg Sub-district, Indramayu District and in the Village of Pangkalanpari, Jatitujuh Sub-district, Majalengka District. The research method consisted of surveys, field data collection such as soil moisture observation, climate data, flowering, harvesting, rainfall relationship analysis with soil moisture, generative phase characteristics or flowering and mango harvesting times. The results showed that the optimal flowering in Krasak village occurred on 4 September 2003 as much as 35.50%, in Sliyeg Lor village occurred on 29 September 2003 of 77.30% and in Pangkalanpari village on 21 August 2003 35.52%. Early harvest of mango gedong gincu showed difference, so did the quality, average weight each mango in Krasak village 211 g, diameter 6.31 cm and length 7.797 cm and in Sliyeg Lor Village 300 g, diameter 7.75 cm and 8.88 cm long, in Pangkalanpari Village 252 g, diameter 7.16 cm and length 8.18 cm. The results show that there is a correlation between rainfall with soil moisture level and flowering rate. The development of mango gedong gincu is done on an areas that has the same climatic conditions, especially the rainfall pattern and the distribution of the soil and done gradually in accordance with harvest time and peak harvest.